2020
DOI: 10.1002/ece3.6988
|View full text |Cite
|
Sign up to set email alerts
|

Demographic consequences of changing body size in a terrestrial salamander

Abstract: Worldwide assessments predict that 15%-37% of terrestrial species will be at risk of extinction by 2050 (Thomas et al., 2004;Tilman et al., 2017). Several mechanisms of extinction predict associated changes in body size due to climate change (Baudron et al., 2014;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Taken together, these ideas support the use of this and similarly structured IPMs for investigating biphasic amphibian population dynamics, as well as amphibian population dynamics more broadly (Hernández‐Pacheco et al, 2021). The model presented in this contribution provides a general structure within which individual functions can be altered for investigations of ecologically similar species.…”
Section: Discussionsupporting
confidence: 62%
“…Taken together, these ideas support the use of this and similarly structured IPMs for investigating biphasic amphibian population dynamics, as well as amphibian population dynamics more broadly (Hernández‐Pacheco et al, 2021). The model presented in this contribution provides a general structure within which individual functions can be altered for investigations of ecologically similar species.…”
Section: Discussionsupporting
confidence: 62%
“…Some studies suggest that changes in body size may follow Bergmann’s rule with increasing temperatures leading to reduced body sizes (Daufresne et al 2009 ; Yom-Tov et al 2010 ) as an adaptation to warmer environments because the larger surface area to volume ratio leads to heat loss (Bergmann 1847 ). On the other hand, the large individual body size is often linked to high individual fitness, specifically to increased fecundity (Chamaillé-Jammes et al 2006 ; Ozgul et al 2010 ; Hernández‐Pacheco et al 2021 ). Shrinking body size in response to climate change could therefore be maladaptive and thus threaten populations of species where large body size is connected to higher individual fitness and thus ultimately population persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Over long periods of evolutionary time, body size generally increases within a given lineage (Heim et al, 2015; Hone et al, 2005; Raia et al, 2012) so recent observations of size declines in several taxa (Daufresne et al, 2009; Ozgul et al, 2009) have been cause for concern. Such size declines can have profound and long‐lasting effects across multiple scales of biological organization, from individuals to ecosystems (Alberti et al, 2017; Hernández‐Pacheco et al, 2021; Woodward et al, 2005), and much work has focused on understanding the patterns of size declines (Gardner et al, 2011; Sheridan & Bickford, 2011), as well as the driving mechanisms behind the observed trends (Gardner et al, 2019; Sheridan et al, 2018). Climate change has been suggested as the likely driver of recently observed size changes, but several studies suggest that land use change may also contribute to recently observed size changes.…”
Section: Introductionmentioning
confidence: 99%